A Novel and Efficient Iterative Approach to Approximating Solutions of Fractional Differential Equations - Doaa Filali; Nidal H. E. Eljaneid; Adel Alatawi; Esmail Alshaban; Montaser Saudi Ali; Faizan Ahmad Khan (Mathematics)
This study presents a novel and efficient iterative approach to approximating the fixed points of contraction mappings in Banach spaces, specifically approximating the solutions of nonlinear fractional differential equations of the Caputo type. We establish two theorems proving the stability and convergence of the proposed method, supported by numerical examples and graphical comparisons, which indicate a faster convergence rate compared to existing methods, including those by Agarwal, Gursoy, Thakur, Ali and Ali, and <semantics>D∗∗</semantics>. Additionally, a data dependence result for approximate operators using the proposed method is provided. This approach is applied to achieve the solutions for Caputo-type fractional differential equations with boundary conditions, demonstrating the efficacy of the method in practical applications.